The Effectiveness Of “PhET INTERACTIVE SIMULATION” In Improving Multi-Mode Representations (MMRs) Embeddedness And Translation In Learning Chemical Equilibrium Among Matriculation Students - Ganasen, Sumathi (2020)
This study investigated the effectiveness of “PhET” interactive simulations to embed and translate multi-mode representations and effectiveness of embedding and translating multi-mode representations on students’ misconceptions and retention of knowledge in chemical equilibrium. This study also investigated students’ flow experiences towards learning chemistry. Concurrent embedded mixed method design was employed for four weeks among 140 Matriculation students. The effectiveness of “PhET” interactive simulations to encourage the embedding and translating multimode representations measured using Chemical Equilibrium Open Ended Questions (CEOEQ). The Chemical Equilibrium Diagnostic Instrument (CEDI) measured students’ misconceptions and retention of knowledge in chemical equilibrium while Students’ Flow Experiences Questionnaire (SFEQ) measured students’ flow experiences towards learning chemistry. The MANCOVA analysis performed indicates that PhET interactive simulations significantly improved multi-mode representations embeddedness in CEOEQ open ended test ((F (1,134) = 603.925, P <0.00, n2 = 0.818) and improved translation between multi-mode representations (F (1,137) = 473.784, P <0.00, n2= 0.776).